Determinants of High-Dose Insulin Usage and Upper Extremity Muscle Strength in Adult Patients With Type 2 Diabetes - YAVUZ, DİLEK; APAYDIN, TUĞÇE (ELSEVIER, 2021)
Objectives: In this study, we aimed to determine the association between upper extremity muscle strength and insulin dose in patients with type 2 diabetes. Methods: A total of 236 patients with type 2 diabetes under insulin treatment for at least 1 year were included in this cross-sectional study. Patients were divided into 3 groups based on their total daily insulin dose (TDID): group 1, TDID >2 U/kg/day or >200 units/day; group 2, TDID 1 to 2 U/kg/day or 51 to 199 U/day; and group 3, TDID <0.5 U/kg/day or 50 U/day. High-dose insulin use was defined as total daily insulin dose >2 U/kg or >200 U/day. Muscle strength was measured using a handgrip dynamometer. Results: High-dose insulin users were younger and had higher measures of generalized and central obesity and glycated hemoglobin. There was no significant difference in muscle strength between the groups. Low muscle strength was seen in 26.7% of all patients. Patients with low muscle strength were older, had lower insulin dose treatment and had better glycemic control than patients with normal muscle strength. Handgrip strength was inversely correlated with age, body mass index and duration of diabetes, but not with TDID. Conclusions: Patients with type 2 diabetes with high-dose insulin use had similar upper extremity muscle strength measurements with standard-dose insulin users. Studies with more patients are needed to determine the relationship between muscle mass, muscle strength and high-dose insulin use. (c) 2020 Canadian Diabetes Association.
Keywords: diabetes mellitus; insulin; muscle strength; type 2; upper extremity; SKELETAL-MUSCLE; OLDER-ADULTS; RESISTANCE; HEALTH; U-500; RISK; SARCOPENIA; REDUCTION